Simulation of the long-term fate of superparamagnetic iron oxide-based nanoparticles using simulated biological fluids - Rabel, Martin; Warncke, Paul; Gruettner, Cordula; Bergemann, Christian; Kurland, Heinz-Dieter; Mueller, Robert; Dugandzic, Vera; Thamm, Jana; Mueller, Frank A.; Popp, Juergen; Cialla-May, Dana; Fischer, Dagmar (Nanomedicine, 2019)
Aim: To simulate the stability and degradation of superparamagnetic iron oxide nanoparticles (MNP) in vitro as part of their life cycle using complex simulated biological fluids. Materials & methods: A set of 13 MNP with different polymeric or inorganic shell materials was synthesized and characterized regarding stability and degradation of core and shell in simulated biological fluids. Results: All MNP formulations showed excellent stability during storage and in simulated body fluid. In endosomal/lysosomal media the degradation behavior depended on shell characteristics (e.g., charge, acid-base character) and temperature enabling the development of an accelerated stress test protocol. Conclusion: Kinetics of transformations depending on the MNP type could be established to define structure-activity relationships as prediction model for rational particle design.
CRIS-Team Scopus Importer:2020-10-13
Keywords: degradation; long-term fate; lysosome/endosome; prediction model; SPION; stability; superparamagnetic iron oxide nanoparticles